INDICADORES DE BIENESTAR ANIMAL EN BOVINOS ANTES Y DURANTE EL FAENAMIENTO, EN EL CAMAL MUNICIPAL DE QUEVEDO, AÑO 2022 - Velásquez Robles, Shirley Michelle (2023)
Animal welfare indicators in bovines were evaluated before and during slaughter, in the municipal slaughterhouse of Quevedo canton. Forms were designed to collect the information. To determine the sample size, random sampling was applied, obtaining a sample of 169 animals. The results indicate that during the investigation the entry of 369 animals from La Mana, Santo Domingo, Pucayacu and Valencia was registered. Upon arrival of the cattle, there were no injured or dead animals.